2007
DOI: 10.1111/j.1742-4658.2007.05898.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of chitinase‐like proteins (Cg‐Clp1 and Cg‐Clp2) involved in immune defence of the mollusc Crassostrea gigas

Abstract: Glycoside hydrolase family 18 (GH18) is a phylogenetically conserved group of proteins present in eukaryotes, prokaryotes and viruses. The GH18 family is characterized by a Glyco_18 domain adopting an (a ⁄ b) 8 triose phosphate isomerase-barrel structure that consists of a specific arrangement of eight parallel b-strands, forming the barrel core, surrounded by eight a-helices [1]. This family classification, based only on similarities in amino acid sequences, groups together chitinases and proteins devoid of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
29
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 33 publications
3
29
0
Order By: Relevance
“…The upregulated expression of Le-chitinase in L. elliptica following injury is in line with findings in the oyster C. gigas (Badariotti et al 2006(Badariotti et al , 2007a. mRNA levels of chitinases increased in the hemocytes of C. gigas following bacterial challenge and involvement in development, tissue growth, and remodeling was reported.…”
supporting
confidence: 85%
“…The upregulated expression of Le-chitinase in L. elliptica following injury is in line with findings in the oyster C. gigas (Badariotti et al 2006(Badariotti et al , 2007a. mRNA levels of chitinases increased in the hemocytes of C. gigas following bacterial challenge and involvement in development, tissue growth, and remodeling was reported.…”
supporting
confidence: 85%
“…The full-length cDNA contained a polyadenylation signal (AATAAA) in the 3'-end UTR, which is common among the mRNAs of inflammatory molecules (Shen et al, 2011). The low levels of sequence identity in the C-terminal regions, probably caused by the relatively low selection pressure during evolution, may contribute little to the structure and function of CLPs (Badariotti et al, 2007). The observations that My-Clp1 contained conserved domain structures and architectures, such as the Glyco_18 domains and active centers, provide further evidence for the high degree of sequence conservation of this gene throughout its evolutionary history because all CLPs from other selected species exhibited the same domains based on amino acid sequence homology.…”
Section: Discussionmentioning
confidence: 99%
“…This result is not in agreement with those reported for C. gigas, which indicate a relatively low expression level in the muscle tissue. Furthermore, it was reported that the Chit2 gene was highly expressed in the muscle tissue (Badariotti et al, 2006(Badariotti et al, , 2007(Badariotti et al, , 2011. This may be due to the lack of expression during specific stages of growth and indicates that the biological activities may be spatially partitioned among the family members.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations